A novel double agent of triazole-based zinc-containing complex which constituted Zn/Zn stabilizer system with zinc stearate as thermal stabilizer for poly(vinyl chloride). (October 2019) - Ma, Biao; Wang, Xu; Lu, Songyan; He, Huiwen; Ma, Meng; Shi, Yanqin; Chen, Si
Abstract: An effectively Zn/Zn stabilizer system instead of traditional Ca/Zn stabilizer system was put forward, which contained a new triazole-based zinc-containing complex (abbreviated as [Zn(ttr)(St)]) and Zinc stearate (ZnSt2 ). Without Ca soap in the system, [Zn(ttr)(St)] itself could effectively absorb HCl and provided PVC with higher transparency and better thermal stability without "zinc burning" than commercial CaSt2 /ZnSt2 stabilizer system, verified by Congo red tests and discoloration tests and dynamic thermal stability analysis. In addition, [Zn(ttr)(St)] could further delay "zinc burning" of other zinc soaps, constituting Zn/Zn stabilizer system. This is attributed to the strong ability of restricting ZnCl2 of 3-amino-1, 2, 4-triazole released from [Zn(ttr)(St)] after absorbing HCl. After adding ESBO, PVC stabilized by [Zn(ttr)(St)]/ZnSt2 /ESBO showed excellent transparency and thermal stability. We believe that [Zn(ttr)(St)] can act as a novel double agent with the stabilization effects of zinc soap and calcium soap at the same time and this Zn/Zn stabilizer system may inaugurate a new stabilizer system for PVC with synergistic effect. Highlights: A novel triazole-based zinc-containing complex([Zn(ttr)(St)]) with 2D layered frameworks was successfully synthesized. Single [Zn(ttr)(OAc)] showed better stabilization effect than commercial Ca/Zn stabilizer with no "zinc burning". Just like calcium soap, [Zn(ttr)(St)] could also delay "zinc burning" caused by other zinc soaps when used with others. PVC stabilized by [Zn(ttr)(St)]/ZnSt2 /ESBO showed excellent thermal stability and transparency. When stabilizing PVC, [Zn(ttr)(St)] absorbed HCl and then released 3-amino-1, 2, 4-triazole which is another stabilizer.